2005
DOI: 10.1161/01.hyp.0000150859.47929.8e
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Blood Pressure Measurement in Humans and Experimental Animals

Abstract: Abstract-Accurate measurement of blood pressure is essential to classify individuals, to ascertain blood pressure-related risk, and to guide management. The auscultatory technique with a trained observer and mercury sphygmomanometer continues to be the method of choice for measurement in the office, using the first and fifth phases of the Korotkoff sounds, including in pregnant women. The use of mercury is declining, and alternatives are needed. Aneroid devices are suitable, but they require frequent calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
963
1
60

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,054 publications
(1,039 citation statements)
references
References 146 publications
9
963
1
60
Order By: Relevance
“…1 However, not surprisingly, the deflation rate of 2.5 mm s ƀ1 was found to be most accurate for SBP, as it has previously been shown that faster deflation rates are likely to underestimate SBP. 19 One possible advantage in selecting a different deflation rate relates to the suggestion that measurement accuracy at a set deflation rate is influenced by heart rate.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…1 However, not surprisingly, the deflation rate of 2.5 mm s ƀ1 was found to be most accurate for SBP, as it has previously been shown that faster deflation rates are likely to underestimate SBP. 19 One possible advantage in selecting a different deflation rate relates to the suggestion that measurement accuracy at a set deflation rate is influenced by heart rate.…”
Section: Discussionmentioning
confidence: 79%
“…The automated mode provides an alternative to auscultation when Korotkoff sounds are poor and eliminates terminal digital preference and observer bias, as well as the error incurred with rapid manual deflation rates. 1 However, as severe accuracy limitations have been shown with oscillometric BP Validation of Nissei DM-3000measurement in certain sub-populations, 5-8 these participants would benefit from the manual measurement mode of this device. The blinded measurement mode is a feature of devices such as the PMS Mandhaus 14 and A&D UM-101, 12 and although it has been reported to underestimate BP, we recognized the clinical benefit that such a measurement mode could offer.…”
Section: Discussionmentioning
confidence: 99%
“…Resting systolic (SBP) and diastolic (DBP) blood pressure were assessed in the population study using a hospitalā€grade automated blood pressure monitor using a standard protocol (Omron 5 Series Upper Arm [BP742]) 30. Participants were sitting, legs uncrossed, with arms not restricted by clothing and relaxed, for at least 5Ā minutes before measurements were taken.…”
Section: Methodsmentioning
confidence: 99%
“…We followed general recommendations on selecting cuff size to ensure that the bladder length was B80% and width was X40% of the arm circumference, covering the upper arm without obscuring the antecubital fossa. 21 Three separate BP measurements were taken, and averaged for analysis. Mean arterial BP (MABP) was calculated as one-third of the systolic plus two-thirds of the diastolic BP.…”
Section: Study Populationmentioning
confidence: 99%